2017
DOI: 10.1177/0885066617739561
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anemia on Mortality in Mechanically Ventilated Patients With Chronic Obstructive Pulmonary Disease

Abstract: Critically ill patients with COPD requiring invasive mechanical ventilation for acute respiratory failure without anemia on admission had a better overall survival when compared to those with anemia. No difference was noted in the 90-day mortality. Further studies are needed to determine the impact of the trajectory of hemoglobin on mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 26 publications
(25 reference statements)
1
13
0
Order By: Relevance
“…However, there is no consensus on whether this standard is clinically relevant in COPD patients . In the current study, standards for diagnostic criteria (hemoglobin level <120 g/L for both men and women) for anemia in COPD patients requiring IMV were based on published literature …”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…However, there is no consensus on whether this standard is clinically relevant in COPD patients . In the current study, standards for diagnostic criteria (hemoglobin level <120 g/L for both men and women) for anemia in COPD patients requiring IMV were based on published literature …”
Section: Discussionsupporting
confidence: 89%
“…In our study, the 90‐day all‐cause mortality rate was 33.9% (38/112). However, Rasmussen et al reported that 90‐day mortality in COPD patients requiring IMV was 35.1% (78/222). Gadre et al reported that 90‐day mortality in COPD patients requiring IMV was 43.0% (476/1107), and that hospital mortality in COPD patients requiring IMV was 30% (204/670) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations